Copper and manganese co-mediated cascade aza-Michael addition/cyclization and azidation of 1, 3-enynes: regioselective synthesis of fully substituted azido pyrroles. Issue 43 (28th October 2020) - Ge, Junying; Ding, Qiuping; Yang, Man; He, Tian; Peng, Yiyuan
Abstract : A Cu and Mn co-mediated aerobic oxidative cyclization and azidation reaction of 1, 3-enynes with amines and trimethylsilyl azide has been developed to synthesize fully substituted azido pyrroles. Abstract : An efficient Cu and Mn co-mediated aerobic oxidative cyclization and azidation reaction of 1, 3-enynes with amines and trimethylsilyl azide (TMSN3 ) for the synthesis of fully substituted azido pyrroles has been developed. The three-component reaction has the characteristics of high regioselectivity, wide substrate scope, and mild reaction conditions. A preliminary mechanism for this transformation is proposed.